2014
DOI: 10.1111/ijcp.12363
|View full text |Cite
|
Sign up to set email alerts
|

The long-term cost-effectiveness of varenicline (12-week standard course and 12 + 12-week extended course) vs. other smoking cessation strategies in Canada

Abstract: The standard and extended courses of varenicline are decidedly cost-effective treatment regimes compared with alternative smoking cessation interventions and can provide significant cost savings to the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…A significant part of the intervention was smoking cessation programmes, either pharmacotherapy 4, 5, 36, 37, 38, 40, 41, 48, 50, 51, 53, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, behavioural therapy 6, 42, 47, 66, 67, 68, 69 or a combination of these 33, 34, 35, 43, 45, 46, 49, 52, 54, 70, 71, 72, 73, 74, 75. Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant part of the intervention was smoking cessation programmes, either pharmacotherapy 4, 5, 36, 37, 38, 40, 41, 48, 50, 51, 53, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, behavioural therapy 6, 42, 47, 66, 67, 68, 69 or a combination of these 33, 34, 35, 43, 45, 46, 49, 52, 54, 70, 71, 72, 73, 74, 75. Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 23 of 64 studies reported QALY as their main outcome 5, 35, 38, 40, 41, 47, 48, 49, 56, 58, 59, 61, 62, 63, 65, 69, 70, 76, 78, 81, 86, 88, 94, followed by life years (LY) gained ( n  = nine of 64) 33, 43, 46, 66, 67, 68, 73, 74, 89 or a combination of these ( n  = 12 of 64) 4, 6, 35, 36, 37, 39, 42, 44, 57, 77, 80, 83. Five of 64 studies reported disability adjusted life years (DALY) as their main outcome 60, 82, 90, 91, 92, and only four of 64 (incremental) net benefit 52, 53, 55, 71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of CEAs 39 identified 4 studies published in the past 10 years which compared varenicline, bupropion, or NRT to each other or to standard of care. 20 , 26 , 57 , 58 All but one of these studies 58 also used the BENESCO model but none adjusted to account for safety outcomes. In agreement with our findings, the studies consistently found varenicline to be the most cost-effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In up to one year of dosing, maintenance treatment with varenicline and counseling has been reported to be effective for sustained abstinence (Evins et al, 2014; Tonstad et al, 2006) and a cost-effective alternative to a 12-week treatment course. (Knight et al, 2012; von Wartburg et al, 2014). The demonstrated safety, tolerability, efficacy, and cost-effectiveness of maintenance varenicline make it an attractive option to improve long-term abstinence for smokers with and without SBD.…”
Section: Discussionmentioning
confidence: 99%